Feasibility of exercise and weight management for people with hip osteoarthritis and overweight or obesity: A pilot study. Issue 3 (September 2021) - Hall, Michelle; Spiers, Libby; Knox, Gabrielle; Hinman, Rana S.; Sumithran, Priya; Bennell, Kim L.
Abstract: Objective: Determine the feasibility of a 6-month exercise and weight management intervention for people with hip osteoarthritis (OA). Design: 18 participants with clinical and radiographic hip OA with a body mass index ≥28 ​kg/m 2 and <41 ​kg/m 2 participated. Six consultations with a physiotherapist and six consultations with a dietitian via videoconferencing over six months to deliver, and support, an exercise program and a ketogenic very low-calorie diet with meal replacements. Recruitment rate and retention rate, adherence, adverse events and intervention acceptability were assessed. Overall hip pain, physical function and body weight were assessed via numeric rating scale (NRS, 0–10), Western Ontario and McMaster Universities Osteoarthritis Index physical function subscale (WOMAC, 0–68) and home-scales respectively, at baseline, 3 and 6 months. Results: Eighteen (11% of 157 people screened) participants were enrolled and 16 (89%) completed 6-month assessments. Participants reported acceptable adherence to the intervention. Most (88%) participants were "extremely satisfied" with the intervention. Ten minor adverse events were exercise related. Overall hip pain reduced by −1.9 units (95%CI -2.8 to −0.9) at 3 months and by −3.3 (−4.3 to −2.2) at 6 months. Physical function improved by −8.5 units (95%CI -13.2 to −3.6) and −14.2 (−18.1 to −7.5) at 3 and 6 months respectively. Body weight reduced by 9.8% [95%CI -12% to −8%] and 11.3% [-13.6% to −9%] at 3 and 6 months respectively. Conclusions: The feasibility of a large clinical trial evaluating this exercise and weight management intervention is supported.